Innate Immunity Induces the Accumulation of Lung Mast Cells During Influenza Infection - Zarnegar, Behdad; Westin, Annika; Evangelidou, Syrmoula; Hallgren, Jenny (Frontiers in Immunology, 2018)
Mast cells release disease-causing mediators and accumulate in the lung of asthmatics. The most common cause of exacerbations of asthma are respiratory virus infections such as influenza. Recently, we demonstrated that influenza infection in mice triggers the recruitment of mast cell progenitors to the lung. This process starts early after infection and leads to the accumulation of mast cells. Previous studies showed that an adaptive immune response was required to trigger the recruitment of mast cell progenitors to the lung in a mouse model of allergic inflammation. Therefore, we set out to determine whether an adaptive immune response against the virus is needed to cause the influenza-induced recruitment of mast cell progenitors to the lung. We found that influenza-induced recruitment of mast cell progenitors to the lung was intact in Rag2-/- mice and mice depleted of CD4+ cells, implicating the involvement of innate immune signals in this process. Seven weeks after the primary infection, the influenza-exposed mice harbored more lung mast cells than unexposed mice. As innate immunity was implicated in stimulating the recruitment process, several compounds known to trigger innate immune responses were administrated intranasally to test their ability to cause an increase in lung mast cell progenitors. Poly I:C, a synthetic analogue of viral dsRNA, induced a TLR3-dependent, and IL-33, induced an ST2-dependent increase in lung mast cell progenitors. In contrast, the influenza-induced recruitment of mast cell progenitors to the lung occurred independently of either TLR3 or ST2, as demonstrated using Tlr3-/- or Il1rl1-/- mice. Furthermore, neutralization of IL-33 in Tlr3-/- mice could not abrogate the influenza-induced influx of mast cell progenitors to the lung. These results suggest that other innate receptor(s) contribute to mount the influx of mast cell progenitors to the lung upon influenza infection. Our study establishes that mast cell progenitors can be rapidly recruited to the lung by innate immune signals. This indicates that during life various innate stimuli of the respiratory tract trigger increases in the mast cell population within the lung. The expanded mast cell population may contribute to the exacerbations of symptoms which occurs when asthmatics are exposed to respiratory infections.